Clinical Evaluation of a Defined Zeolite-Clinoptilolite Supplementation Effect on the Selected Blood Parameters of Patients - Kraljević Pavelić, Sandra; Saftić Martinović, Lara; Simović Medica, Jasmina; Žuvić, Marta; Perdija, Željko; Krpan, Dalibor; Eisenwagen, Sandra; Orct, Tatjana; Pavelić, Krešimir (Frontiers in Medicine, 2022)
The natural clinoptilolite material is an inorganic crystal mineral called zeolite. It has been extensively studied and used in industrial applications and veterinary and human medicine due to positive effects on health. Limited data is available in the scientific literature about its effects on the levels of physiologically relevant minerals in the human organism. Accordingly, we performed a comprehensive and controlled monitoring of the relevant mineral and contaminants levels in human subjects supplemented with a certified clinoptilolite material within three clinical trials with different supplementation regimens. Effects of a registered and certified clinoptilolite material PMA-zeolite on selected mineral and metal levels were determined by standard biochemical methods and inductively coupled plasma mass spectrometry (ICP-MS) in the blood of subjects enrolled in three clinical trials: short-term (28 days, Mineral Metabolism and selected Blood Parameters study MMBP), medium-term (12 weeks, Morbus Crohn study) and long-term (4 years, Osteoporosis TOP study) supplementation. Lower concentrations were observed for copper (Cu) in patients with osteoporosis, which normalized again in the long-term supplementation trial, whereas sodium (Na) and calcium (Ca) levels diminished below the reference values in patients with osteoporosis. In the short- and long-term supplementation trials, increased levels of lead (Pb) were observed in PMA-zeolite-supplemented subjects, which decreased in the continued long-term supplementation trial. Increased levels of aluminium (Al) or Pb attributable to eventual leakage from the material into the bloodstream were not detected 1 h after intake in the short-term supplementation trial. Nickel (Ni) and Al were statistically significantly decreased upon long-term 4-year supplementation within the long-term supplementation trial, and arsenic (As) was statistically significantly decreased upon 12-weeks supplementation in the medium-term trial. Alterations in the measured levels for Na and Ca, as well as for Pb, in the long-term trial are probably attributable to the bone remodelling process. Checking the balance of the minerals Cu, Ca and Na after 1 year of supplementation might be prescribed for PMA-zeolite supplemented patients with osteoporosis.